2022
DOI: 10.3389/fped.2022.915045
|View full text |Cite
|
Sign up to set email alerts
|

Impact on clinical outcomes from transcatheter closure of the Fontan fenestration: A systematic review and meta-analysis

Abstract: BackgroundMeta-analysis of the impact on clinical outcome from transcatheter closure of Fontan fenestration.MethodsCochrane, Embase, MEDLINE, and Open-Gray were searched. Parameters such as changes in oxygen saturation, cavo-pulmonary pressure, maximum heart rate during exercise, exercise duration, and oxygen saturation after fenestration closure were pooled and statistical analysis performed.ResultsAmong 922 publications, 12 retrospective observational studies were included. The included studies involved 610 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…While two systematic literature reviews and meta-analyses on the early outcomes of a Fontan fenestration demonstrated mixed benefit in the immediate post-operative period ( 173 , 174 ), our meta-analyses on later outcomes showed patients required either late closure or creation/reopening of a fenestration made at the time of Fontan completion ( 175 ).…”
Section: Surgical Proceduresmentioning
confidence: 73%
“…While two systematic literature reviews and meta-analyses on the early outcomes of a Fontan fenestration demonstrated mixed benefit in the immediate post-operative period ( 173 , 174 ), our meta-analyses on later outcomes showed patients required either late closure or creation/reopening of a fenestration made at the time of Fontan completion ( 175 ).…”
Section: Surgical Proceduresmentioning
confidence: 73%
“…Two systematic literature reviews and meta-analysis have focused upon the early outcomes of a Fontan fenestration, demonstrating a mix benefit in the immediate period, with reduced amount of chest drains and subsequent shorter stay in hospital as the only positive aspects ( 15 , 16 ). Our meta-analysis instead focused on late outcomes, with patients requiring either late closure or creation and/or reopening of a fenestration made at the time of Fontan completion ( 17 ). We found that, following fenestration closure, there was a significant increase in the mean arterial oxygen saturation of 7.9% [95% confidence interval (CI): 6.4–9.4%, P<0.01], at expense of a significant increase in the mean cavo-pulmonary pressure of 1.4 mmHg (95% CI: 1.0–1.8 mmHg, P<0.01) ( 17 ).…”
mentioning
confidence: 99%
“…Our meta-analysis instead focused on late outcomes, with patients requiring either late closure or creation and/or reopening of a fenestration made at the time of Fontan completion ( 17 ). We found that, following fenestration closure, there was a significant increase in the mean arterial oxygen saturation of 7.9% [95% confidence interval (CI): 6.4–9.4%, P<0.01], at expense of a significant increase in the mean cavo-pulmonary pressure of 1.4 mmHg (95% CI: 1.0–1.8 mmHg, P<0.01) ( 17 ). The literature data for fenestration creation and/or reopening didn’t allow any meaningful conclusion ( 17 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations